Analisis Semiotika Roland Barthes Pesan Moral Pada Film Avatar: The Last Airbender (Live Action) Episode 8 - Harahap, Nisrina Adilah; Efendi, Erwan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Movies are generally only considered as a form of entertainment, but movies can also contain messages hidden by their creators, and Avatar: The Last Airbender (Live Action) Episode 8. In this movie, there are many moral messages that we can learn from. This research aims to describe what moral messages are contained in the movie. The method used in this research is descriptive qualitative research method. This research describes a boy named Aang who is an airbender but it turns out he is an Avatar. This research also tells how great Aang is in fighting the Fire Nation without fear. The data collection techniques in this research are: watching movies, writing and observing the behavior of characters and sentences in the data, classifying related data by paying attention to moral messages, and drawing conclusions. The results obtained from this study are as follows: (1) Helping and cooperating can alleviate and overcome problems. (2) Never giving up will bring good results.